2021
DOI: 10.3390/heritage4040173
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological Sites as Peripheral Destinations. Exploring Big Data on Fieldtrips for an Upcoming Response to the Tourism Crisis after the Pandemic

Abstract: Archaeological heritage sites constitute the most recent addition to the tourism supply of Madrid, one of the most visited regions of Spain. In 2003, the Plan de Yacimientos Visitables (Plan of Archaeological Visitable Sites) was implemented, museumising 21 sites. However, the peripheral nature of these sites and the lack of personnel prevent strict control being carried out of who visits them, the practices of these visitors and how they rate the sites. This study proposes a systematic procedure to analyse th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Regarding the research on children's emotional cognition ability, relevant scholars conducted individual tests on children aged 3-9 and conducted in-depth research on children's emotional cognition, helping activities and helping tendencies under different cues [23,24]. The study found that with the increase of age, emotional cognitive performance also gradually increased; children were more likely to recognize tasks with a single situational and expression cue, but more difficult to recognize conflicting cues; with age, children's independent judgment gradually replaced [25][26][27]. The dependence of expression and situation is reduced; too difficult cue tasks will affect children's helping activities and tendencies.…”
Section: Discussion On Emotional Cognition Emotional Cognition Is An ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the research on children's emotional cognition ability, relevant scholars conducted individual tests on children aged 3-9 and conducted in-depth research on children's emotional cognition, helping activities and helping tendencies under different cues [23,24]. The study found that with the increase of age, emotional cognitive performance also gradually increased; children were more likely to recognize tasks with a single situational and expression cue, but more difficult to recognize conflicting cues; with age, children's independent judgment gradually replaced [25][26][27]. The dependence of expression and situation is reduced; too difficult cue tasks will affect children's helping activities and tendencies.…”
Section: Discussion On Emotional Cognition Emotional Cognition Is An ...mentioning
confidence: 99%
“…Throughout the research on emotional cognition, it can be seen that researchers have achieved fruitful results in both empirical and theoretical research on emotional cognition and have provided psychological researchers with a more complete and operational research model [ 13 , 27 ]. However, there are still many problems that need to be solved in the research related to emotion cognition.…”
Section: Discussionmentioning
confidence: 99%
“…The lifestyle of the people has changed, impacting the sites of archaeological heritage [50,51]. Currently, digital technologies are important in the communication between the heritage and the public [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…The driver of Spain's economic and social development is tourism (OECD, 2020b), with using heritage as new proximity tourism routes (Martínez-Hernández et al, 2021). The share of foreign exchange income generated from tourism in 2019 amounted 14% of GDP, while the following year it recorded a big drop to only 5% (see Table 2).…”
Section: Key-characteristics Of Selected Countries Related To the Tou...mentioning
confidence: 99%